The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/14756366.2016.1217853
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-based matrix metalloproteinase inhibitors with additional antioxidative activity

Abstract: New catechol-containing chemical entities have been investigated as matrix metalloproteinase inhibitors as well as antioxidant molecules. The combination of the two properties could represent a useful feature due to the potential application in all the pathological processes characterized by increased proteolytic activity and radical oxygen species (ROS) production, such as inflammation and photoaging. A series of catechol-based molecules were synthesized and tested for both proteolytic and oxidative inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
2
27
2
1
Order By: Relevance
“…As several articles have already described the coordination of metals by pyrazines [44,45], we investigated whether the pyrazine in our compounds could coordinate the Zn 2+ ion in the MMP-8. This could promote potential inhibitory activity on MMP-8, as presented by Tauro et al [43]. We tested this hypothesis using molecular docking studies.…”
Section: Exploring Potential Targets and Activities Using Docking Stumentioning
confidence: 82%
See 2 more Smart Citations
“…As several articles have already described the coordination of metals by pyrazines [44,45], we investigated whether the pyrazine in our compounds could coordinate the Zn 2+ ion in the MMP-8. This could promote potential inhibitory activity on MMP-8, as presented by Tauro et al [43]. We tested this hypothesis using molecular docking studies.…”
Section: Exploring Potential Targets and Activities Using Docking Stumentioning
confidence: 82%
“…We then docked our compound into GTPase KRas, with no interesting results. Finally, matrix metalloproteinase-8 (MMP-8; also known as neutrophil collagenase; PDB ID: 5h8x), was investigated in more detail, where its recently described inhibitors are of the above-mentioned structural type (Ar-SONH 2 -Ar) [43]. This endopeptidase is a part of a very complex proteolytic MMP enzyme family, where its overexpression was linked to several pathological processes [43].…”
Section: Exploring Potential Targets and Activities Using Docking Stumentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted on properties of MMP inhibitors that contain a catechol group in their structures revealed that the catechol oxygens do not coordinate with the zinc ion; they are able to coordinate with zinc ion through one of the oxygen atoms only if they acquire the form of quinone. [ 47 ]…”
Section: Resultsmentioning
confidence: 99%
“…Compared to VMP proteins, MMP proteins has been studied extensively, and many structures exist for MMPs. Close examination of the crystal structure of inhibitor bound MMP8 reveals that the zinc ion in the catalytic site is coordinated by three histidine residues and one catechol inhibitor N-(3,4-dihydroxyphenyl)-4-diphenylsulfonamide 19 . This crystal structure of MMP8 is shown in Figure 1A.…”
Section: Introductionmentioning
confidence: 99%